Adenovirus-Mediated Over-Expression of Nrf2 Within Mesenchymal Stem Cells (MSCs) Protected Rats Against Acute Kidney Injury - Mohammad Mohammadzadeh-Vardin; Mehryar Habibi Roudkenar; Ali Jahanian-Najafabadi (Tabriz University of Medical Sciences, 2015)
Purpose: Recent developments in the field of cell therapy have led to a renewed interest in treatment of acute kidney injury (AKI). However, the early death of transplanted mesenchymal stem cells (MSCs) in stressful microenvironment of a recipient tissue is a major problem with this kind of treatment. The objective of this study was to determine whether overexpression of a cytoprotective factor, nuclear factor erythroid-2 related factor 2 (Nrf2), in MSCs could protect rats against AKI. Methods: The Nrf2 was overexpressed in MSCs by recombinant adenoviruses, and the MSCs were implanted to rats suffering from cisplatin-induced AKI. Results: The obtained results showed that transplantation with the engineered MSCs ameliorates cisplatin-induced AKI. Morphologic features of the investigated kidneys showed that transplantation with the MSCs in which Nrf2 had been overexpressed significantly improved the complications of AKI. Conclusion: These findings suggested that the engineered MSCs might be a good candidate to be further evaluated in clinical trials. However, detailed studies must be performed to investigate the possible carcinogenic effect of Nrf2 overexpression.